Clinical and Anatomical Substantiation of Access to the Splenic and Left Renal Veins in the Operation of Distal Splenorenal Anastomosis - A. Yu. Anisimov; A. I. Andreev; R. A. Ibragimov; A. A. Аnisimov; I. A. Kalimullin (Неотложная медицинская помощь, 2021)
Aim of study. Development in an anatomical experiment of a technique for operative access to the splenic and left renal veins during distal splenorenal bypass surgery with justification of the possibility of its successful application in clinical conditions.Material and methods. In the conditions of an anatomical experiment on 40 unfixed corpses of adults of both genders, objective volumetric and spatial indicators in surgical wounds were studied in two variants of exposure of retroperitoneal space vessels, as the first stage of distal splenorenal anastomosis. In clinical conditions in 40 patients with portal hypertension of various genesis, during the operation of distal splenorenal anastomosis, the wide exposure of the anterior surface of the pancreas, spleen, left renal veins and most of their branches was performed using the original method of partial left — sided medial visceral rotation, followed by an objective assessment of the volume-spatial parameters of access. Measurements were performed using a medical goniometer in relation to the mobilized areas of the left renal and splenic veins. Statistical processing of the study results was carried out using the method of variation statistics. To identify statistically significant differences, the Student’s t-test was used for disjoint samples.Results. An original method of operative access to the splenic and left renal veins was developed during the operation of distal splenorenal bypass by lifting the internal organs of the left flank of the abdominal cavity from the posterior abdominal wall and diverting them to the right. In the anatomical experiment in the original method of partial left-sided medial visceral rotation, all indicators were better (depth of the wound is less and the angles of operative activity and the inclination of the axis of operative activity — larger) than with a classic approach of intraoperative intraperitoneal access via transverse incision in the mesentery of the transverse colon. Despite the various variants of vascular architectonics and various anthropometric indicators of patients, there were no any forced refusal of distal splenorenal bypass surgery or unintentional damage to both the vessels themselves and the pancreas, specific complications associated with the implementation of the proposed operative approach to the vessels of the left retroperitoneal space, including damage to the spleen and ischemia of the descending colon, in any of 40 clinical cases.Conclusion. The suggested option of operative access to the splenic, left renal veins and their branches at the first stage of performing distal splenorenal anastomosis in patients with portal hypertension of various genesis provides convenient spatial relations in the operating wound; creates comfortable conditions for performing the main surgical technique — applying vascular anastomosis; has a minimal risk of developing specific complications associated with the approach to the vessels of the left retroperitoneal space.